Immunogenicity of a 20-valent pneumococcal conjugate vaccine in adults 18 to 64 years old with medical conditions and other factors that increase risk of pneumococcal disease - Charu Sabharwal; Vani Sundaraiyer; Yahong Peng; Lisa Moyer; Todd J. Belanger; Bradford D. Gessner; Luis Jodar; Kathrin U. Jansen; William C. Gruber; Daniel A. Scott; Wendy Watson (Human Vaccines & Immunotherapeutics, 2022)
The aim of this post hoc analysis was to describe the immunogenicity of the 20-valent pneumococcal conjugate vaccine (PCV20) in adults with chronic medical conditions or smoking that place them at increased risk of developing pneumococcal disease. Data from 2 phase 3, randomized, active-controlled, double-blind studies in pneumococcal vaccine-naive adults were analyzed. Study 1: adults ≥18 years were enrolled in 1 of 3 age-based cohorts (18‒49, 50‒59, and ≥60 years) and randomized (1:1, adults ≥60 years; 3:1, younger cohorts) to receive 1 dose of PCV20 or 13-valent PCV (PCV13). Participants ≥60 years who received PCV13 were administered 23-valent polysaccharide vaccine 1 month later. Study 2: adults 18‒49 years were randomized (2:2:2:1) to receive 1 dose of PCV20 from 1 of 3 lots or PCV13. Opsonophagocytic activity (OPA) titers were measured in sera collected before and 1 month after vaccination. We investigated immune responses of PCV20 among participants 18‒64 and 18‒49 years of age with ≥1 medical condition or other factor (smoking) that increases the risk of serious pneumococcal disease. Of 4369 participants overall (PCV20, n = 2975; PCV13, n = 1394), 1329 participants (30%) had ≥1 risk factor; most commonly smoking, diabetes, and chronic pulmonary disease. Among participants with risk factors, substantial increases in OPA geometric mean titers were observed across the 20 vaccine serotypes from before vaccination to 1 month after PCV20. Robust immune responses to all 20 vaccine serotypes 1 month after PCV20 were observed in adults with increased risk of serious pneumococcal disease. Clinical trial registration NCT03760146, NCT03828617.